Simple wet-chemical synthesis of superparamagnetic CTAB-modified magnetite nanoparticles using as adsorbents for anionic dye Congo red removal - Eksuree Saksornchai (2018)
© 2017 Elsevier B.V. Magnetite (Fe 3 O 4 ) and Fe 3 O 4 coated with cetyltrimethylammonium bromide (CTAB) were successfully synthesized by simple wet-chemical method. The results show that the products were Fe 3 O 4 nanoparticles. The saturation magnetization and BET method reveal these nanoparticles exhibited superparamagnetic behavior with high surface area. So, it is a very potential application for using as adsorbents for anionic dye Congo red (CR) removal. Its adsorption capacity, calculated by Langmuir isotherm, is 93.46 mg/g. Furthermore, the pseudo-second order model and intra-particle diffusion model (IPD) were also investigated.